Do Concomitant Posterior Malleolus Fractures Affect Mid-Term Functional Outcomes in Tibial Shaft Fractures?. Issue 4 (November 2022) - Bastias, Gonzalo F.; Ignacio Quezada Morales, Jose; Gutierrez, Paulina; Diaz, Felipe G.; Melo, Rodrigo; Cuchacovich Mikenberg, Natalio R.; Munoz, Gerardo; Filippi, Jorge
Category: Trauma; Ankle Introduction/Purpose: The association between diaphyseal tibial fractures and posterior malleolus fracture has been reported between 4 to 25% of cases. Early diagnosis requires a high level of suspicion and may change the surgical strategy. To our knowledge, no studies had compared the functional and quality of life results of tibial fractures with and without posterior malleolus extension. Methods: A retrospective comparative study including patients sustaining tibial shaft fractures classified by AO type 42, 43A, and 43B1.1, with a minimum one-year follow-up. Exclusion criteria included open fractures, pathological bone fractures and patients with a previous history of ipsilateral bone injury. Patients were divided into two groups, tibial shaft injuries with posterior malleolus fracture (PM) and fractures without posterior malleolus fracture (WPM) diagnosed using computed tomography (CT) preoperatively. The posterior malleolus fracture was fixed before the tibial fracture, either with 1 or 2 percutaneous anteroposterior or posteroanterior screws. Postoperative CT was used to assess the quality of reduction in all patients. Functional and quality of life results were evaluated using the Lower Extremity Function Score (LEFS), visual pain analog scale (VAS), and Short Form (SF12). We compared times of return to work/sports, complications and additional procedures during follow-up. Shapiro-Wilk test and Student t-test were used for statistical analysis. Results: Twenty patients in the PM group and 22 in the WPM group were included with a mean follow-up of 43 months (R:8-43). Groups were demographically comparable, with an average age of 47.6 and 43.3 years (p:0.34), respectively. All fractures healed, CT showed an anatomical articular reduction in all patients. Tibial shaft fracture was treated with intramedullary nailing in 15 patients of the WPM group and seven patients in the PM group. Percutaneous medial plating was used in the rest of the cases. At final follow-up, LEFS score in the PM group was 73.6 vs. 70.6 in the WPM group, with no significant difference (p:0.23). There were also no significant differences in VAS scale, time of return to work and sports in both groups. The PM group scored better in physical (p:0, 02) and mental (p:0, 01) SF-12. Conclusion: In this series of closed tibial shaft fractures, the presence of a posterior malleolus fracture did not affect functional results, time to return to work, or return to sports. Moreover, the SF-12 was superior in the PM group. All patients in the PM group had a timely diagnosis and anatomical reduction, which probably influenced the good clinical results. There were no additional procedures or degenerative complications in the PM group.